A COMPARATIVE STUDY OF COGNITIVE PROCESSING IN ORAL MATHEMATICS TESTS AMONG MALAYSIAN ORANG ASLI PUPILS (Malaysian Journal of Learning and Instruction, 2025)
Purpose – This study investigates the mathematics performance of Orang Asli pupils across two cognitive domains—Knowing and Applying—using three oral mathematics tests developed in different languages: the academic language (Bahasa Melayu) (OBM), the academic native language (Bahasa Semai) (OSL), and the tribal native language (Bahasa Temiar) (OTL).Methodology – Adopting a quantitative approach, the study involved 225 Year 4 Orang Asli pupils who were assessed using a 20-item mathematics computation testlet. The analysis focused on pupils’ performance across the Knowing and Applying domains in the three oral test formats (OBM, OSL, and OTL). One-way Analysis of Variance (ANOVA) was used to compare performance differences across the cognitive domains and test formats.Findings – In the Knowing domain, pupils performed best in the OSL test, followed by OBM and OTL. Conversely, in the Applying domain, pupils excelled in the OTL test, followed by OSL and OBM. ANOVA results indicated significant differences between OSL and OTL, as well as OBM and OTL in the Knowing domain. However, no significant difference was found between OSL and OBM. For the Applying domain, a significant difference was observed only between OTL and OBM, with no significant differences between OTL and OSL, or between OSL and OBM.Significance – The findings highlight the potential of oral mathematics tests in native languages—particularly Bahasa Semai—as a culturally responsive and equitable assessment method. This approach enables Orang Asli pupils to better demonstrate their mathematical proficiency helping to address linguistic barriers in mathematics assessment.